Impact of prior treatment on patients with relapsed multiple myeloma treated with carfilzomib and dexamethasone vs bortezomib and dexamethasone in the phase 3 ENDEAVOR study - Moreau, P (Leukemia, 2017)
The randomized phase 3 ENDEAVOR study (N=929) compared carfilzomib and dexamethasone (Kd) with bortezomib and dexamethasone (Vd) in relapsed multiple myeloma (RMM). We performed a subgroup analysis from ENDEAVOR in patients categorized by number of prior lines of therapy or by prior treatment. Median progression-free survival (PFS) for patients with one prior line was 22.2 months for Kd vs 10.1 months for Vd, and median PFS for patients with ⩾2 prior lines was 14.9 months for Kd vs 8.4 months for Vd. For patients with prior bortezomib exposure, the median PFS was 15.6 months for Kd vs 8.1 months for Vd, and for patients with prior lenalidomide exposure the median PFS was 12.9 months for Kd vs 7.3 months for Vd. Overall response rates (Kd vs Vd) were 81.9 vs 65.5% (one prior line), 72.0 vs 59.7% (⩾2 prior lines), 71.2 vs 60.3% (prior bortezomib) and 70.1 vs 59.3% (prior lenalidomide). The safety profile in the prior lines subgroups was qualitatively similar to that in the broader ENDEAVOR population. In RMM, outcomes are improved when receiving treatment with carfilzomib compared with bortezomib, regardless of the number of prior therapy lines or prior exposure to bortezomib or lenalidomide.